2014
DOI: 10.1371/journal.pone.0095128
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Highly Active Xylanase Displaying Oleaginous Yeast: Comparison of Anchoring Systems

Abstract: Three Yarrowia lipolytica cell wall proteins (YlPir, YlCWP1 and YlCBM) were evaluated for their ability to display the xylanase TxXYN from Thermobacillus xylanilyticus on the cell surface of Y. lipolytica. The fusion proteins were produced in Y. lipolytica JMY1212, a strain engineered for mono-copy chromosomal insertion, and enabling accurate comparison of anchoring systems. The construction using YlPir enabled cell bound xylanase activity to be maximised (71.6 U/g). Although 48% of the activity was released i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Nevertheless, recent studies by Duquesne et al . () and Boonvitthya et al . () showed pTEF promoter to be useful in efficient heterologous expression of xylanases and cellulases in Y. lipolytica .…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, recent studies by Duquesne et al . () and Boonvitthya et al . () showed pTEF promoter to be useful in efficient heterologous expression of xylanases and cellulases in Y. lipolytica .…”
Section: Resultsmentioning
confidence: 87%
“…XPR2 and Lip2 pre‐ and prepro‐signal peptides are the most commonly used in heterologous protein production in Y. lipolytica . These sequences were found to be highly efficient in directing the protein to the extracellular space (Boonvitthya et al ., ; Duquesne et al ., ; Madzak et al ., ). On the other hand, it has been reported that some signal peptides, native for the heterologous protein itself, may lead the protein to the secretory pathway of Y. lipolytica cells.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is one of the most abundant hemicelluloses in lignocellulosic materials and therefore its use as a carbon source is desirable for biotechnology due to its low costs. Xylanases, the enzymes that break xylan down into xylose, have been expressed in Y. lipolytica; they have been either secreted into growth media [43] or displayed on cell surfaces [56]. However, a discrepancy in the engineered strain's ability to grow on xylose has been seen in the literature.…”
Section: Xylanmentioning
confidence: 99%
“…However, a discrepancy in the engineered strain's ability to grow on xylose has been seen in the literature. On the one hand, although xylanase originating from Thermobacillus xylanilyticus and displayed on cell surfaces was used to determine the efficiency of three different anchoring systems, yeast growth on xylan was not observed [56]. On the other hand, Trichoderma harzianum endo-1,4-b-xylanase (XynII) and A. niger exo-1,4-b-xylosidase xlnD were successfully independently secreted and together allowed strains to grow on xylan [43].…”
Section: Xylanmentioning
confidence: 99%